Evaluation of Application Effects of Nitrogen Levels under Drought Stress Condition on Physiological Characteristics and Yield of Kochia (Kochia scoparia) in Saline Agriculture - L Kooshki; H. R Khazaei; M Kafi; M Goldani (پژوهشهای زراعی ایران, 2024)
IntroductionNowadays, the cultivation of plants adapted to adverse conditions, such as drought and salinity, in the country has been considered. Meanwhile, Kochia scoparia, one of the forgotten plants, due to its classification in the group of halophytes, has specific characteristics suitable for cultivation in low-water and saline areas (Salehi, Kafi, & Kiani, 2012). This plant is known as an important annual forage crop, and its grains also have high nutritional value and oil, which can be considered for future industrial applications (Salehi et al., 2012). Studies on the salinity tolerance of the Kochia plant have shown that it is suitable for cultivation in saline areas, and in terms of quantity and quality, can compete with conventional forage plants. The use of natural organic materials, such as humic acid, has received more attention. These materials, as part of soil organic matter, are influenced by physical, chemical, and microbiological changes in biological molecules (Sabzevari & Khazaei, 2009; Dong, Córdova-Kreylos, Yang, Yuan, & Scow, 2009). Additionally, nitrogen is the most important element needed for plant growth and development. It is also a key component in many biological compounds, including proteins, nucleic acids, some hormones, and chlorophyll. Nitrogen plays an essential role in photosynthetic processes and the final function of plants (Kaur, Gupta, & Kaur, 2002; Taiz, Zeiger, Møller, & Murphy, 2015). As a result of this research, a combination of nitrogen and humic acid can be used as nutritional resources in salt stress conditions.Materials and MethodsThis experiment was conducted in the form of split plots based on the randomized complete block design with three replications in the Saline Research Farm of Ferdowsi University of Mashhad in the 2015 growth season. The main plot included drought stress with a four-week interruption of irrigation at three levels of control (irrigation until the end of the growing season), after establishment (50 days after planting), the beginning of flowering (71 days after planting) and late flowering (82 days after planting) The subplot was included nitrogen application at three levels of zero, 100 and 200 kg.ha-1 from urea fertilizer source. The optimum level of humic acid (2 per thousand) was done as seed at the time of planting for all treatments.Results and DiscussionThe results showed that the drought stress during vegetative and reproductive growth stages had a negative effect on the Kochia plant. However, its effect in the early stages of vegetative growth (after establishment) was greater than the stress at the end of the season (late flowering). Drought stress has a negative effect on Kochia grain yield by reducing the concentration of chlorophyll a, altering the chlorophyll a to b ratio, decreasing carotenoid concentration, and affecting relative leaf water content. However, seed treatments of humic acid and its combination with 100 kg.ha-1 nitrogen level by increasing the concentration of total phenol, soluble carbohydrate concentration, and DPPH free radical scavenging capacity improved photosynthetic pigments and finally kochia grain yield. In general, the most suitable treatment for use in drought stress and saline water source conditions was the combined method of sowing humic acid seeds with 100 kg.ha-1 nitrogen fertilizer.ConclusionIn general, the occurrence of drought stress in vegetative and reproductive growth stages had a negative effect on the kochia plant. However, its effect in the early stages of vegetative growth (after establishment) was greater than the stress at the end of the season (late flowering). The most suitable treatment was using the combined method of seed of humic acid with 100 kg.ha-1 nitrogen fertilizer..